Product Market Competition, Financial Leverage, Risk of Financing on Financial Stability: Studies on Islamic Banks in Indonesia - Duwi Ira Setianti; Slamet Haryono (Jurnal Ekonomi Syariah Teori dan Terapan, 2023)
ABSTRACT This study aims to explain and analyze the effect of product market competition, financial leverage, and risk of financing on the stability of Islamic banks in Indonesia in 2018-2022.  The sampling technique used is Islamic banks listed on the Indonesia Stock Exchange.  Source of data obtained from the annual report of each bank.  The analytical method used is panel regression analysis with Eviews 10 software with the Common Effect Model (CEM) model as the best model. The variables used consist of product market competition (PCM), financial leverage (DER proxy), and financing risk (NPF proxy) on banking stability (proximate Natural Logarithm Z-Score).  The results of this study found that product market competition did not affect bank stability.  Meanwhile, financial leverage and financing risk have a negative effect on the stability of Islamic banks in Indonesia.  From the results of this study, it is hoped that competition for Islamic banks in Indonesia can always run normally as it is today.  In addition, the financial leverage and financing risks of Islamic banks have a negative impact on banking stability.  Therefore, this research can be used as an early warning and reference for Islamic banks to make funding decisions through debt capital and excessive financing. keywords: Banking stability, product market competition, financial leverage, financing risk ABSTRAK  Penelitian ini bertujuan untuk menjelaskan dan menganalisis pengaruh persaingan pasar produk, financial leverage, dan risk of financing terhadap stabilitas bank syariah di Indonesia pada 2018-2022. Teknik pengambilan sampel yang digunakan bank syariah yang terdaftar di Bursa Efek Indonesia. Sumber data diperoleh dari laporan tahunan masing masing bank. Metode analisis yang digunakan adalah analisis regresi panel dengan software Eviews 10 dengan model Common Effect Model (CEM) sebagai model terbaik .Variabel yang digunakan terdiri dari persaingan pasar produk (PCM), financial leverage (proksi DER) dan resiko pembiayaan (proksi NPF) terhadap stabilitas perbankan (doproksikan Natural Logarithm Z-Score. Hasil dari penelitian ini menemukan bahwa persaingan pasar produk tidak berpengaruh terhadap stabilitas bank. Sementara financial leverage dan resiko pembiayaan berpengaruh negative terhadap stabilitas bank syariah di Indonesia. Dari hasil penelitian ini, diharapkan persaingan bank syariah di Indonesia dapat selalu berjalan berjalan normal seperti saat ini. Selain itu, financial leverage dan resiko pembiayaan bank syariah berdampak buruk pada stabilitas perbankan. Oleh karena itu, penelitian ini dapat dijadikan early warning dan acuan bagi bank syariah untuk mengambil keputusan pendanaan melalui modal hutang dan pembiayaan yang berlebihan. Kata Kunci: Stabilitas perbankan, product market competition, financial leverage, resiko pembiayaan